1996
DOI: 10.1136/bmj.313.7054.407
|View full text |Cite
|
Sign up to set email alerts
|

Fortnightly Review: Neonatal screening for sickle cell disorders: what about the carrier infants?

Abstract: Summary points Neonatal screening for sickle cell disorders detects between 17 and 100 carrier infants for each child detected as having sickle cell disorder Information on neonatal carrier status is an unavoidable outcome of the neonatal screening process Withholding information from parents is not justified Further research is needed to evaluate the benefits and risks of this information and the effectiveness of different policies for follow up This is relevant to future developments in molecular genetics, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…This unintended information may include information about the genetic carrier status of a newborn infant, for example, as occurs in newborn sickle cell screening programmes. 236 Alternatively, it may include the detection of milder variants of 'disease' which may have little functional implications for the individual concerned but which cannot be ignored by the parents or the health professional delivering screening.…”
Section: Rationale and Criteria For Evaluating Newborn Screening Progmentioning
confidence: 99%
“…This unintended information may include information about the genetic carrier status of a newborn infant, for example, as occurs in newborn sickle cell screening programmes. 236 Alternatively, it may include the detection of milder variants of 'disease' which may have little functional implications for the individual concerned but which cannot be ignored by the parents or the health professional delivering screening.…”
Section: Rationale and Criteria For Evaluating Newborn Screening Progmentioning
confidence: 99%
“…There is little previous evidence on acceptable and effective methods of communicating carrier status and more research is needed. 17,18 Previous research has suggested that people are reluctant to disclose carrier status when arranging marriages. [19][20][21] This study's findings differ significantly; many of the responders wanted to know about carrier status before choosing a partner and recommended openness.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Whether learning about a carrier state is a benefit or cost of newborn screening has been a matter of debate. Some have argued that newborn screening programs should report results on carrier status (78,79) and that these findings represent an ancillary benefit of testing (54)(55)(56). Others argue that routine reporting of carrier results violates the right ''not to know'' and is of no direct benefit to the infant (80).…”
Section: Challenges In Evaluating Newborn Screening Resultsmentioning
confidence: 99%